Mapping of Tax Avoidance Behavioral Patterns in The Digital Business Environment (Implications for Tax Regulations and Financial Risk Management) - Arum, Mega; Kurniawan , Hendra (ProBisnis : Jurnal Manajemen, 2025)
The development of digital technology has significantly affected the business landscape, including in terms of taxation. In the context of digital business, the phenomenon of tax avoidance has become a major concern. This study aims to understand the pattern of tax avoidance behavior in the digital business environment and analyze its implications for tax regulations and financial risk management. The research method used involves literature analysis to identify common patterns of tax avoidance behavior in digital businesses. The results of the analysis show that digital businesses often take advantage of loopholes in tax regulations to reduce their tax obligations, either through transfer pricing, entity location determination, or profit shifting practices. The implications of this behavior are very complex, including challenges in enforcing relevant tax regulations and managing financial risks for affected countries. This study also highlights the importance of cross-border cooperation in addressing the tax challenges faced by digital businesses. While international tax regulations have evolved to accommodate the changing business environment, there is still a need for further reform to address increasingly complex tax avoidance practices. This study proposes several policy recommendations, including increasing cooperation between countries in the exchange of tax information, the use of technology to detect and prevent tax avoidance, and updating tax regulations that are more adaptive to the development of digital businesses. Thus, this study contributes to a better understanding of the dynamics of tax avoidance in the context of digital business and provides useful insights for policy makers, practitioners and academics in addressing this challenge.